Colicin M is an inhibitor of murein biosynthesis. - Schaller, K (American Society for Microbiology (ASM), 1982)
Colicin M inhibited the incorporation of DL + meso-2,6-diamino[3,4,5-3H]pimelic acid into the murein (peptidoglycan) of growing cells of Escherichia coli W7 dap lys. The inhibition of the UDP-N-acetylmuramyl pentapeptide-dependent incorporation of UDP-N-acetyl-D-[U-14C]glucosamine into isolated cell envelopes indicated interference with a late step of murein biosynthesis. After the inhibition of murein biosynthesis, cells lysed, and they released lysis products of murein. In vitro, the murein biosynthesis of colicin M-tolerant mutants (tolM) was inhibited by colicin M. Therefore, tolerance is probably conferred by an impaired uptake of an altered fixation close to the target site and not by a mutation of the target itself. Preliminary studies with beta-lactam antibiotics and with mutants in penicillin-binding proteins did not reveal a specific enzymatic step inhibited by colicin M. The unique action among the colicins renders colicin M a potentially useful tool for studying murein biosynthesis.